Numerical weather prediction or stochastic modelling: an objective criterion of choice for the global radiation forecasting. (2016) - Voyant, Cyril; Notton, Gilles; Paoli, Christophe; Nivet, Marie-Laure; Muselli, Marc; Dahmani, Kahina
Numerous methods exist and were developed for global radiation forecasting. The two most popular types are the numerical weather predictions (NWPs) and the predictions using stochastic approaches. We propose to compute a parameter noted χ constructed in part from the mutual information which is a quantity that measures the mutual dependence of two variables. Both of these are calculated with the objective to establish the more relevant method between NWP and stochastic models concerning the current problem.